Religion and the Relationship Between Verbal Aggressiveness and Argumentativeness - Crouchera, Stephen M. (2012)
This study analyzes the influence of sex, education, religion, and religiosity on the relationship between argumentativeness and verbal aggressiveness. Verbal aggressiveness is a less acceptable way to approach disagreement than argumentativeness. Argumentativeness and verbal aggressiveness were not significantly related. Further analysis revealed that male participants were significantly more verbally aggressive, individuals with higher education were less verbally aggressive, and religiosity decreased verbal aggressiveness. Moreover, Mainline Protestants were generally more verbally aggressive than other religious groups.